Draft Genome Assembly of Floccularia luteovirens, an Edible and Symbiotic Mushroom on Qinghai-Tibet Plateau. Issue 4 (1st April 2020) - Gan, Xiaolong; Cao, Dong; Zhang, Zhenyu; Cheng, Shu; Wei, Le; Li, Shiming; Liu, Baolong
Abstract: Floccularia luteovirens, also known as "Yellow mushroom", is an edible ectomycorrhizal fungus widely distributed in the Qinghai-Tibet Plateau alpine meadow. So far, little genomic information is known about F. luteovirens, which is not conductive to the protection and utilization of it. In this manuscript, we present a first draft genome assembly and annotation of F. luteovirens . The fruiting body of F. luteovirens was sequenced with PacBio Sequel and Illumina Hiseq 2500 system. The assembled genome size was 28.8 Mb, and comprising 183 contigs with a N50 contig size of 571 kb. A total of 8, 333 protein-coding genes were predicted and 7, 999 genes were further assigned to different public protein databases. Besides, 400 CAZymes were identified in F. luteovirens . Phylogenetic analysis suggested that F. luteovirens should belong to the Agaricaceae family. Time tree result showed that the speciation of F. luteovirens happened approximately 170 Million years ago. Furthermore, 357 species-specific gene families were annotated against KEGG and GO database. This genome assembly and annotation should be an essential genomic foundation for understanding the phylogenetic, metabolic and symbiotic traits of F. luteovirens .